2008
DOI: 10.1592/phco.28.10.1267
|View full text |Cite
|
Sign up to set email alerts
|

Anemia of Critical Illness

Abstract: Anemia of critical illness, a commonly encountered clinical situation, is hematologically similar to that of chronic anemia, except that the onset is generally sudden. The etiology is usually multifactorial, occurring as a consequence of direct inhibitory effects of inflammatory cytokines, erythropoietin deficiency, blunted erythropoietic response, blood loss, nutritional deficiencies, and renal insufficiency. Although anemia is not well tolerated by critically ill patients, aggressive treatment of anemia can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 158 publications
(162 reference statements)
2
21
0
Order By: Relevance
“…Sprung et al found that fulfilling more than two criteria carries a higher risk of subsequent development of severe sepsis, septic shock and MODS (19) . This finding was confirmed by Rangel-Frausto et al who stated that "SIRS with only two criteria -as initially proposed -is less helpful in defining a subset of ICU and ward patients who are at especially high risk of severe sepsis than SIRS with three or all four criteria" (17) Our findings regarding anaemia in sepsis patients is consistent with the accumulating evidence that anaemia in critically ill patients is common and correlates with poor outcome (20,21) . The mechanism of anaemia in these patients is similar to that of chronic disease anaemia, except that the onset is generally rapid (21) .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Sprung et al found that fulfilling more than two criteria carries a higher risk of subsequent development of severe sepsis, septic shock and MODS (19) . This finding was confirmed by Rangel-Frausto et al who stated that "SIRS with only two criteria -as initially proposed -is less helpful in defining a subset of ICU and ward patients who are at especially high risk of severe sepsis than SIRS with three or all four criteria" (17) Our findings regarding anaemia in sepsis patients is consistent with the accumulating evidence that anaemia in critically ill patients is common and correlates with poor outcome (20,21) . The mechanism of anaemia in these patients is similar to that of chronic disease anaemia, except that the onset is generally rapid (21) .…”
Section: Discussionsupporting
confidence: 84%
“…This finding was confirmed by Rangel-Frausto et al who stated that "SIRS with only two criteria -as initially proposed -is less helpful in defining a subset of ICU and ward patients who are at especially high risk of severe sepsis than SIRS with three or all four criteria" (17) Our findings regarding anaemia in sepsis patients is consistent with the accumulating evidence that anaemia in critically ill patients is common and correlates with poor outcome (20,21) . The mechanism of anaemia in these patients is similar to that of chronic disease anaemia, except that the onset is generally rapid (21) . Despite the deleterious effect of anaemia of critical illness, aggressive treatment with blood products can be as detrimental as no treatment with associated increase in morbidity and mortality (21,22) .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Anemia of chronic disease, as has been known for decades, accompanies many chronic disease states, in which inflammation is frequent, such as cancer, chronic infection and autoimmune diseases [2]. Recently, the same form of anemia has been detected in patients with acute critical illness – anemia of critical illness [3]. Therefore, the new term ‘anemia of inflammation’ was proposed instead of anemia of chronic disease since it better defines the underlying pathophysiology, namely the central role of inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…The causes of anemia are multifactorial and include direct inhibitory effects of inflammatory cytokines, erythropoietin deficiency, poor endogenous erythropoietin response, altered iron metabolism, pathogen-associated hemolysis, overt and occult bleeding, iatrogenic blood loss through diagnostic phlebotomy, nutritional deficiencies, renal insufficiency and treatment causing bone marrow suppression. These causes may be grouped into three main categories: decreased red blood cell (RBC) production, increased RBC destruction, and blood loss [2]. Different types of anemia frequently coexist in critically ill pediatric patient.…”
mentioning
confidence: 99%